Grit and self-discipline as predictors of effort and academic attainment - Hagger, Martin; Hamilton, K. (2018)
Background: Beyond ability, traits related to perseverance, such as grit and self-discipline, are associated with adaptive educational outcomes. Few studies have examined the independent effects of these traits on outcomes and the mechanisms involved. Aims: This study estimated parameters of a process model in which grit-perseverance of effort (grit-effort) and consistency of interest (grit-interest) dimensions and self-discipline were independent predictors of students’ science grades. The effect of the grit-effort on grades was expected to be mediated by students’ self-reported effort on optional out-of-school science learning activities. Sample: Secondary school students (N = 110) aged between 12 and 14 years. Methods: The study adopted a correlational design with measures taken on three occasions. Students completed self-report measures of grit and self-discipline early in the semester and effort on optional out-of-school learning activities 5 weeks later. Students’ science grades were collected at the end of the semester. Data were analysed using Bayesian path analyses using non-informative and informative priors derived from previous research. Results: Consistent with predictions, we found effects of grit-effort on science grades mediated by effort, and self-discipline on grades. Contrary to predictions, we also found an effect of self-discipline on grades mediated by effort. Zero was a credible value for direct effects of grit-effort on grades, and grit-interest on effort and grades. Conclusions: Results suggest grit-effort and self-discipline relate to effort on educational activities linked to better grades. The direct effect of self-discipline on grades suggests that it may be related to other activities that determine science attainment.